KEPATUHAN MINUM OBAT PADA PAIEN TB PARU - Malik Fajar Rozaqi; Sulistyo Andarmoyo; Yayuk Dwi Rahayu (Health Sciences Journal, 2018)
AbstactDrug Compliance Drugs in Pulmonary TB Patients in the Work Area of Kunti Puskesmas and Puskesmas Kauman Kabupaten PonorogoBy: Malik Fajar RozaqiThe level of adherence in treatment is a dynamicacomplex phenomenon withaa variety of factors that impact on patient behavior in treatment. Inadequate health care, understanding, and compliance with amedication areathe main obstacles to findingaeffective solutions.aThis study aims to determine the adherence of medication to patients in pulmonary tuberculosis in the area of Puskesmas Kunti and Puskesmas Kauman Ponorogo RegencyThe studyadesign was descriptive, with a total population ofaall pulmonaryaTB patients of 37 patients. The sample sizeawas 37 patients and thearesearch method was using Total Sampling. Data collection usingaquestionnaire, data in show with percentage.From thearesult of thearesearch at Puskesmas Kunti 14 respondents and Puskesmas Kauman 23 respondents so total of 37 respondents concluded 17 respondents (45,94%) have high compliance attitude, 12 respondents (32,43%) have medium compliance attitude and 8 respondents (21, 62%) have low compliance attitudes.From the research it can be concluded that pulmonary tuberculosis patients have obedient attitude in the medication adherence of pulmonary tuberculosis. It is hoped that patients with pulmonary tuberculosis will increase their adherence in taking pulmonary TB drugs so that the treatment can be achieved.Keywords: Adherence, Drinking, Patient, Drugs, Pulmonary TBAbstrakKepatuhan Minum Obat PadaaPasienaTB Paru di Wilayah Kerja Puskesmas Kunti dan Puskesmas KaumanaKabupatenaPonorogoaOleh: Malik Fajar RozaqiTingkat kepatuhan dalam pengobatan merupakanasebuahafenomena kompleks yang dinamisdenganberbagaifaktoryang berdampak pada perilaku pasienadalamapengobatan. Pelayanankesehatanyang tidakmenyeluruh,pemahaman,dan kepatuhan pengobatan yang kurang menjadi kendala besar untuk menemukan solusiyangefektif. Penelitian ini bertujuan untuk mengetahui “kepatuhan minum obat pada pasien TB paru” di wilayah Puskesmas Kunti dan Puskesmas Kauman Kabupaten PonorogoDesain penelitian adalahadeskriptif, dengan populasi seluruh pasien TB paru sejumlah 37 pasien.aBesarasampel 37 pasien danametode penelitian menggunakan Total Sampling. Pengumpulan data menggunakan kuisioner, data di tampilkan dengan prosentase.Dari hasilapenelitian di Puskesmas Kunti 14 responden dan Puskesmas Kauman 23 responden jadi total sejumlah 37 responden disimpulkan 17 responden (45,94%) memiliki sikap kepatuhan tingggi, 12 responden (32,43%) memiliki sikap kepatuhan sedang dan 8 responden (21,62%) memiliki sikap kepatuhan rendah.Dari penelitian dapat di simpulkan bahwa pasien TB paru memiliki sikap patuh dalam kepatuhan minum obat TB paru. Diharapkan pasien TB paru lebih meningkatakan kepatuhan dalam minum obat TB paru agar pegobatan dapat tercapai. Kata Kunci: kepatuhan , Minum, Pasien, Obat, TB Paru